The Effect of Brand Strategy and Pricing in Increasing Customer Loyalty of Electric Cigarette - cita, mutia; Derriawan; Sari, Lola Fitria (Krisnadwipayana International Journal of Management Studies, 2025)
This study aims to explore the influence of Product Quality, Brand Image and Price on Customer Satisfaction and Customer Loyalty in e-cigarette products. This study identified that the largest number of e-cigarette users are in the age range of 21-30 years (Generation Z). The main factors that influence customer satisfaction and loyalty among this generation include product quality, brand image, and price. This is due to the tendency of Generation Z to be very sensitive to product quality, brand trust, and price considerations in making purchasing decisions. This study uses a qualitative approach by conducting in-depth interviews with regular e-cigarette consumers and analyzing customer satisfaction and loyalty towards e-cigarette products. The findings show that quality products affect customer satisfaction and loyalty, in addition, a positive brand image, supported by a good product image and user image will form strong brand values, quality products with a strong brand image will affect customer satisfaction and loyalty if the product has a competitive price, contributing significantly to customer satisfaction and loyalty. The practical implications of this study are the importance of product quality, brand image and price as a strategy to increase long-term customer satisfaction and loyalty in e cigarette products in the Indonesian cigarette industry. This study also needs to know that there needs to be quality control of a product and maintaining a positive image of a product by setting competitive prices on e-cigarettes is very helpful in increasing the satisfaction and loyalty of e-cigarette customers. Customer satisfaction and loyalty are investments from an industry to expand the target market of a product.